Trade Finance In Digital Era: Can Fintech Harness The Current Risks And Challenges? - Safeza Mohd Sapian; Nurudeen Abdulkadir; Norhazlina Ibrahim (USIM Press (Penerbit USIM), 2024)
Trade and commercial activities are the foundation and supporting pillars of the global economy. It is through trade, particularly international trade, that a country’s economy is developed and sustained. It is a fact that FinTech platforms help financial service providers to become more time and cost-efficient in delivering trade finance services, however, the moves come with a high price. As the system becomes complex, the risks associated with it are also high due to systemic vulnerabilities, hackers and security hurdles. This current state requires more rigorous risk identification and management systems along with proficient internal control system, especially for international trade and trade financing. It has propelled many financial intermediaries to be more competitive in committing to the development of digitised channels and propositions, preparing to cede market share to a new generation of providers that have already seized the imperative to respond to market evolution in international trade. The main aim of this paper is to explore how far can FinTech platforms help the financial service providers to be more efficient in providing their services to the end-user while at the same time be excellent to harness the possibilities of cyber and FinTech risk in this digital era. The study reviews past studies done in this area, especially on the risks and challenges, the prospects and opportunities of FinTechs in trade financing and its ability to cope with the risks inherent in FinTech solutions. The findings show that the benefits of FinTech platforms outweigh the shortcomings and with sustained collaboration, standardization and a holistic approach to the development of FinTech solutions, the risks of digital transformations can be considerably reduced.